POLA PENGEMBANGAN INDUSTRI PERIKANAN TANGKAP DI KABUPATEN INDRAMAYU MENGGUNAKAN PENDEKATAN ANALISIS PERSAMAAN STRUKTURAL - Mustaruddin Mustaruddin (Institut Pertanian Bogor, 2009)
Indramayu regency render production rate 54,38% from the total rate production of sea fisheries production in north coastal West Java reaching Rp 216,9 billion per year. Capture fisheries effort can be developed further with maximizing the positive interaction and anticipate negative interaction of the Capture fisheries effort components. The research result show that suistainable of fisheries resources and human quality are the main internal focus of the capture fisheries industry development (kp = 2,41 by P = 0,042). While some components that become main interest for external aspect, governmental policy, and industry development performance is influence of culture (kp = 4,39 by P = 0,024), licensing (kp = 1,63 by P = 0,000), and ability in return of invesment (kp = 4,39 by P = 0,024). The height focus in cultural aspect because of Indramayu fishermen easy to follow behavior changing from outside. From fisherman point of view, the job assurance opportunity must become main focus to development, but the reasing of fisherman earn consider to be disregarded because the profit sharing from every trip remain high enough during this time. Key word: capture fisheries, development, industrial, interaction